Effective Classroom Administration and Management Strategies: A Case Study from Esperanto Milenaka High School, Madagascar: - Ratna, Hangivola Emyblonde; Sadik, Andjarwati; Meirling, Andi; Lewa, Inriati; Indarwati, Indarwati (JOELS: Journal of Election and Leadership, 2025)
Teacher leadership in classroom management plays a central role in creating a conducive and effective learning environment, yet in-depth studies on optimal leadership styles remain scarce. This research explores the relationship between teacher leadership and classroom management strategies, focusing on the approaches employed, student characteristics, and the leadership skills required. Using a descriptive qualitative method, data were collected through field observations, in-depth interviews, and document analysis. The findings reveal that effective leadership in classroom management is characterized by the ability of teachers to design structured learning strategies, make adaptive decisions, and motivate students through approaches tailored to their cognitive and socio-emotional needs. Inclusive and collaborative leadership styles have been shown to enhance classroom discipline, resolve conflicts, and foster positive learning dynamics. This study provides essential insights for teachers and education administrators to develop leadership skills that effectively support the achievement of learning objectives. On a broader scale, strong leadership in classroom management not only improves the quality of classroom interactions but also contributes to the overall improvement of national education quality by fostering a generation of learners who are excellent and highly competitive.